2015
DOI: 10.1021/acs.orglett.5b00339
|View full text |Cite
|
Sign up to set email alerts
|

Base-Stabilized Nitrilium Ions as Convenient Imine Synthons

Abstract: A simple and efficient methodology is presented for the synthesis of a wide range of substituted imines. It is based on stabilizing readily available, but thermally labile, N-alkylnitrilium triflates with pyridine or DMAP to moderately air-stable adducts. These base-stabilized imine synthons react conveniently with phosphorus- and nitrogen-based nucleophiles to amidines and phosphaamidines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 55 publications
2
12
0
Order By: Relevance
“…The molecular structure of 6a shows Rh1–P1, Rh1–N1, and Rh1–Cl1 bond lengths of respectively 2.3123(14), 2.106(4), and 2.3728(13) Å and an acute N1–C1–P1 bond angle of 100.4(4)°. The structural features of 7a resemble those of 6a and other bidentate 1,3-P,N Rh(III) complexes, 17,18a,18b,18d except for its triflate group with an Rh1–O11 bond length of 2.1957(18) Å that is similar to those reported for monodentate Rh(III)–triflate bonds. 26 Expectedly, the S1–O11 bond is elongated with respect to the S1–O12 and S1–O13 bonds: i.e., 1.4711(19), 1.433(2), and 1.429(2) Å, respectively.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…The molecular structure of 6a shows Rh1–P1, Rh1–N1, and Rh1–Cl1 bond lengths of respectively 2.3123(14), 2.106(4), and 2.3728(13) Å and an acute N1–C1–P1 bond angle of 100.4(4)°. The structural features of 7a resemble those of 6a and other bidentate 1,3-P,N Rh(III) complexes, 17,18a,18b,18d except for its triflate group with an Rh1–O11 bond length of 2.1957(18) Å that is similar to those reported for monodentate Rh(III)–triflate bonds. 26 Expectedly, the S1–O11 bond is elongated with respect to the S1–O12 and S1–O13 bonds: i.e., 1.4711(19), 1.433(2), and 1.429(2) Å, respectively.…”
Section: Resultssupporting
confidence: 68%
“…The procedure is analogous to the protocol we reported recently, the difference being that here nitriles 1 are directly alkylated to provide the ion, whereas previously we obtained the ions from imidoyl chlorides. 17 The choice of synthetic approach depends on the N substituent: with i -Pr or larger alkyl groups, imidoyl chlorides are the starting point, sometimes necessitating stabilization of the resulting nitrilium ions with pyridine bases, 17c but smaller groups are only accessible by nitrile alkylation. 22 Thus, treating 1 with MeOTf gave the corresponding N -methyl nitrilium triflates 2 (R = Ph ( a ), 4-CH 3 -C 6 H 4 ( b ), 4-CF 3 -C 6 H 4 ( c )).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed insertion reactivity in complexes 7 and 8 may have potential in catalysis. Since the products are reminiscent of iminium ions (i.e., nitrogen-stabilized N-protic nitrilium ions), which readily undergo nucleophilic attack, this might be exploited in the (catalytic) functionalization of nitriles or terminal triple bonds. , Alternatively, 7 and 8 could serve as, for instance, [(κ 2 -imidoyl-aryl)­Ir III ] transfer hydrogenation catalysts . Overall, it is especially interesting that the reactivity of the NHC H complex changes upon reduction.…”
Section: Resultsmentioning
confidence: 99%
“…37 Recently we have shown that treating thermally labile N-alkyl nitrilium triflates with DMAP renders moderately airstable adducts 27 (Scheme 3), which much improves the handling of the nitrilium ion while retaining their reactivity. 38 For instance, solid DMAP adduct 27 (R = iPr) gave only 9% of the hydrolyzed product upon exposure to air for one month.…”
Section: Stable Nitrilium Saltsmentioning
confidence: 99%